Tax structures and economic growth: New evidence from the Government Revenue Dataset - Kyle McNabb (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Recent work on the relationship between tax structure and economic growth has offered little reliable evidence for developing countries. Yet it is in such countries where the greatest changes in tax structure not only have been seen over the past 30 years but will likely continue to be seen in the future. Thus, an understanding of what, if any, links exist between the tax mix and the long-run economic growth rate is of vital importance to policymakers. Using the Government Revenue Dataset (GRD) from the International Centre for Tax and Development (ICTD), this study considers the effects of revenue-neutral changes in tax structure on a panel of 100 developing and developed countries. The results suggest that the biggest shifts in tax structure seen over the past three decades - i.e. shifts away from trade toward domestic consumption taxes - have had modest positive effects only for those economies classed as lower-middle-income. Furthermore, revenue-neutral increases in personal income taxes or social contributions are found to be harmful for long-run per capita GDP growth rates. These findings call some existing results into question; specifically, this paper finds that the effects of different taxes on growth differ according to income level, calling into question the external validity of existing studies.
Keywords: O11; O23; E62; 330; tax structure; economic growth; fiscal policy; developement